Estrategias lúdicas para la enseñanza aprendizaje de Matemáticas en Educación General Básica superior, Colegio de Bachillerato “27 de Febrero” - Ortiz Garrido, Giomar Alejandra (2024)
Playful strategies are teaching methods used by the teacher to make the learning process more interesting and motivating for the students. This study analyzed how playful strategies contribute to the teaching-learning process of Mathematics in students of Higher General Basic Education. The research with a mixed approach and descriptive scope had a field design; the bibliographic review method was supported with the indexing technique and the search log, bibliographic cards and content cards as instruments, which were used to obtain information that was contrasted with the information obtained through a survey to teachers and students. The bibliographic review showed that the main characteristics of playful strategies are: they improve communication, develop in students mathematical skills, critical thinking and decision-making. From the empirical information it was determined that the teachers of General Basic Education of Mathematics of the “Colegio de Bachillerato 27 de Febrero”, apply playful strategies correctly, however, it was evidenced that they do not diversify them; therefore, their application allows students to be involved in an effective and efficient way in the teaching-learning process of Mathematics. Keywords: Teaching learning, playful strategies, playful strategies, learning of Mathematics.